Perancangan Dan Implementasi Sistem Point Of Sales (POS) Berbasis Web Menggunakan Framework Laravel 11 (Studi Kasus Toko Umkm Nasution) - Razman Rifany; Nunik Pratiwi (Prosiding Seminar Nasional Teknoka, 2024)
Toko Nasution, a small and medium-sized enterprise (SME) in the retail sector, faces challenges in transaction recording and data management using conventional methods, which pose risks of data loss and difficulty in integrating branch operations. The proposed solution is the implementation of a web-based POS system using Laravel 11. The system is designed using the prototype method and employs Unified Modeling Language (UML) for system design. The research began with interviews with the store owner, followed by designing a prototype using Balsamiq 3, which was tested and evaluated by the SME owner. After the prototype was approved, coding and implementation were carried out, followed by Alpha and Beta testing using the black-box method to ensure the system's functionality. The implementation results in reduced data loss risks, easier data-driven decision-making, improved operational efficiency, and increased customer satisfaction. The system also manages data in real-time, and the POS system handles transactions smoothly.